2022
DOI: 10.1055/s-0042-1757595
|View full text |Cite
|
Sign up to set email alerts
|

Knee Arthroscopy Prior to Total Knee Arthroplasty: Temporal Relationship to Surgical Complications

Abstract: Mechanical knee symptoms secondary to knee osteoarthritis (OA) may warrant knee arthroscopy (KA). Degenerative changes may progress and require a subsequent total knee arthroplasty (TKA). Recent studies have evaluated the timing of KA prior to TKA, associated a narrow interval with increased post-TKA complications. However, an updated analysis is required. We compared surgical outcomes in recipients of KA prior to TKA as stratified by four, time-dependent cohorts (< 12, 12 to 16, 16 to 20, and 20 to 24 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…However, our research contributes additional depth by assessing a broader range of risk determinants, such as ASA scores and intraoperative haemorrhage, providing a more comprehensive risk profile for SSIs post‐TKA. Sax et al's 25 evaluation of the timing of knee arthroscopy prior to TKA and associated complications contrasts with our focus on SSIs post‐TKA. While Sax et al concentrate on surgical timing, our study provides a unique contribution by identifying modifiable risk factors, enhancing preoperative assessment protocols.…”
Section: Discussionmentioning
confidence: 90%
“…However, our research contributes additional depth by assessing a broader range of risk determinants, such as ASA scores and intraoperative haemorrhage, providing a more comprehensive risk profile for SSIs post‐TKA. Sax et al's 25 evaluation of the timing of knee arthroscopy prior to TKA and associated complications contrasts with our focus on SSIs post‐TKA. While Sax et al concentrate on surgical timing, our study provides a unique contribution by identifying modifiable risk factors, enhancing preoperative assessment protocols.…”
Section: Discussionmentioning
confidence: 90%
“…We do not know whether TKA after subchondroplasty is associated with a greater risk of serious complications such as infection. Previous studies have found that prior knee arthroscopy followed by TKA is associated with a greater risk of revision, infection, aseptic loosening, and stiffness and that the risk of complications can be related to the duration of time between knee arthroscopy and TKA [1,5]. Because arthroscopy is part of the subchondroplasty procedure, the risk of complications after subsequent TKA could be increased.…”
mentioning
confidence: 99%